1990
DOI: 10.1111/j.1471-4159.1990.tb04915.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Cysteinyl‐Leukotriene Formation in Tissue Slices from Human Intracranial Tumors: Evidence for Their Biosynthesis Under In Vivo Conditions

Abstract: In previous studies, it had been shown that human gray and white matter tissue slices have the capacity to synthesize large amounts of cysteinyl-leukotrienes (cysteinyl-LT) in vitro. This study was initiated to investigate cysteinyl-LT formation by tissue slices from intracranial tumors in comparison with cyclooxygenase products such as prostaglandin (PG) F2 alpha and thromboxane (TX) B2. Tissue slices from meningiomas and astrocytomas were found to release large amounts of cysteinyl-LT spontaneously and even … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
23
0
1

Year Published

1992
1992
2006
2006

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 45 publications
(43 reference statements)
1
23
0
1
Order By: Relevance
“…They have been extensively studied as mediators in the pathobiologic processes of allergic asthma and other respiratory disorders, but little is known on their role and cellular source in the CNS. However, CysLTs levels have been reported to increase in brain injuries, including cerebral ischemia, hemorrhage and epileptic seizures (14,50). Recently we reported that astrocytes and microglia release CysLTs both under resting conditions and following stimulation with the calcium ionophore A23187 or with ATP through P2Y 1 metabotropic receptor subtypes (12,3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have been extensively studied as mediators in the pathobiologic processes of allergic asthma and other respiratory disorders, but little is known on their role and cellular source in the CNS. However, CysLTs levels have been reported to increase in brain injuries, including cerebral ischemia, hemorrhage and epileptic seizures (14,50). Recently we reported that astrocytes and microglia release CysLTs both under resting conditions and following stimulation with the calcium ionophore A23187 or with ATP through P2Y 1 metabotropic receptor subtypes (12,3).…”
Section: Discussionmentioning
confidence: 99%
“…Another group of pro-inflammatory agents, the cysteinyl leukotrienes, (CysLTs), namely LTC4' LTD4 and LTE4' playa role in diverse pathological processes in brain, including seizures, hemorrhage, ischemia and tumors (50,14,51,49). CysLTs are members of a large family of molecules known as eicosanoids whose biosynthesis is triggered by the action of cytosolic phospholipase A2 followed by the action of 5-lipoxygenase and 5-lipoxygenase activating protein (FLAP) on arachidonic acid (9).…”
mentioning
confidence: 99%
“…Cysteinyl leukotrienes (CysLTs) production was consistently increased in cerebrospinal fluid in patients with multiple sclerosis (51) or intracerebral hemorrhage (60) as well as in brain tumors (54).…”
mentioning
confidence: 99%
“…In the first experiment (Fig. 1 Right), the most abundant 5-LO transcripts (2.7, 3.1, and 4.8 kb) were detected in two meningiomas (lanes 1 and 2) 16 hr at 22°C, and 3 days at -70°C. The size of the hybridization bands is indicated in kb.…”
mentioning
confidence: 93%
“…Moreover, administration of leukotriene C4 selectively increases the permeability of the blood-brain barrier in brain tumors (15), suggesting that these molecules may mediate the vasogenic edema associated with brain tumors. Cerebral meningiomas and astrocytomas are hypothesized to release cysteinylleukotrienes to blood at rates that correlate with the grade of malignancy (16). If this were the case, then the level of the 5-LO mRNA in brain tumors may also correlate with malignancy.…”
mentioning
confidence: 99%